Enhancing Language Skills in Golden Age Children through English Phonology - Yani Lubis; Ulysa Humayrah; Afia Nur Meiza; Novita Ritong; M. Farhan Dwiki Nanda; M. Fazlur Rahman (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study explores the significance of English phonology in enhancing language skills during the golden age of childhood. Phonological awareness, encompassing sound discrimination and manipulation, plays a crucial role in vocabulary acquisition, reading proficiency, and overall linguistic development. Early intervention through phonological activities in educational settings, supported by parental involvement and technological integration, fosters a strong foundation for language acquisition. Continuous professional development for educators ensures the implementation of evidence-based practices in phonological instruction. Investing in phonological awareness during childhood is essential for promoting academic success, cognitive development, and lifelong literacy.